Quality Culture (Multicite Study of Sayek H. Abdul Halim Hasan Al-Ishlahiyah Binjai Islamic High School And Jam'iyah Mahmudiyah Tanjung Pura LKAT Islamic High School) - Aswaruddin, Aswaruddin; Mukti, Abdul; Wijaya, Candra (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to reveal and analyze the quality culture at (STAI) Syekh H. Abdul Halim Hasan Al-Ishlahiyah Binjai and STAI Jam'iyah Mahmudiah Tanjung Pura City. The research method used in this research is qualitative research with a multi-site approach. The results of this study are: (1) The implementation of an institutional quality culture in educational institutions has a positive impact on improving service quality. This is reflected in a high level of customer satisfaction, where students are satisfied with the services provided; (2) Culture of good resource quality at STAI Syekh H. Abdul Halim Hasan Al-Ishlahiyah Binjai and STAI Jam' iyah Mahmudiah Tanjung Pura Langkat City is an increase in the quality and performance of human resources as well as an increase in productivity, satisfaction of human resources, and the quality of education services. With clear policies, effective training and development programmes, rigorous recruitment processes, regular performance evaluations and proper performance management policies, educational institutions will achieve a significant positive impact on their progress and success; (3) The implementation of a lecturer and staff development program that focuses on the Tri Dharma of higher education at STAI Syekh H. Abdul Halim Hasan Al-Ishlahiyah Binjai and STAI Jam'iyah Mahmudiah Tanjung Pura Langkat City is that the two tertiary institutions can contribute by collaborating with educational institutions and research institutes, as well as meeting national standards, this tertiary institution is able to maintain the quality of higher education, produce quality graduates, and play an active role in the development of science and society; (4) The availability of adequate facilities and infrastructure at STAI Syekh H. Abdul Halim Hasan Al-Ishlahiyah Binjai and STAI Jam'iyah Mahmudiah Tanjung Pura Langkat City is to improve the quality of education in both institutions and provide good support for student success. With comfortable lecture halls, complete libraries, adequate laboratories and studios, as well as adequate sports and fitness facilities, educational institutions create a conducive and effective learning environment; (5) The steps taken by the leadership of STAI Sheikh H. Abdul Halim Hasan Al-Ishlahiyah Binjai and STAI Jam' iyah Mahmudiah Tanjung Pura Langkat City is the creation of an institutional environment that is transparent, trusted and accountable.Â